STUDY OF DRUG UTILISATION PATTERN IN ACNE VULGARIS IN DERMATOLOGY OUTPATIENT DEPARTMENT OF A TERTIARY CARE HOSPITAL - DOLI CHOUDHURY; PINAKI CHAKRAVARTY; TANUREETO CHOUDHURY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aims of this study were as follows: (1) To study the drug utilization pattern of drugs prescribed to patients suffering from acne vulgaris attending the Outpatient Department of Dermatology at Tezpur Medical College and Hospital. 2 To assess the rationality of prescriptions using the World Health Organization (WHO) core indicators. Acne vulgaris is one of the most common skin disorders, affecting more than 85% of adolescents worldwide. The irrational use of drugs is a significant concern in modern medical practice, as it can lead to ineffective treatment, unnecessary prescriptions, adverse effects, and an economic burden on both patients and society. Results: A total of 2,360 prescriptions were analyzed. A female predominance was observed among the patients, with the most common age group being 21–30 years. The average number of drugs per encounter was 3.21. The percentage of medicines prescribed by generic names was 62.35%, and the percentage of antibiotics prescribed was 29%. The most commonly prescribed antibiotic was doxycycline, and the majority of drugs prescribed were topical (74.32%). Conclusion: This study performed relatively well when compared to other similar studies but still fell short when measured against the optimal values recommended by the WHO. An improvement in the prescribing pattern is necessary to reduce the unnecessary prescription of drugs, enhance the effectiveness of treatment, and lower the cost of treatment.